2014
DOI: 10.1016/j.scitotenv.2013.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Development and review of Euro 5 passenger car emission factors based on experimental results over various driving cycles

Abstract: The emissions of CO2 and regulated pollutants (NOx, HC, CO, PM) of thirteen Euro 5 compliant passenger cars (seven gasoline, six Diesel) were measured on a chassis dynamometer. The vehicles were driven repeatedly over the European type-approval driving cycle (NEDC) and the more dynamic WMTC and CADC driving cycles. Distance-specific emission factors were derived for each pollutant and sub-cycle, and these were subsequently compared to the corresponding emission factors provided by the reference European models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(77 citation statements)
references
References 13 publications
5
63
0
6
Order By: Relevance
“…While diesel engines exhibit some relatively high performances, especially in terms of CO 2 specific emission (g/km) [4], they suffer from the acknowledged dilemma called NO…”
Section: Introductionmentioning
confidence: 99%
“…While diesel engines exhibit some relatively high performances, especially in terms of CO 2 specific emission (g/km) [4], they suffer from the acknowledged dilemma called NO…”
Section: Introductionmentioning
confidence: 99%
“…Low cylinder temperature during engine start and first tip-in of the FTP-75 mode produces more wall-films, which result in significant particle emissions. Optimization of engine control strategy of multiple injections combined with high injection pressure during cold start and cold transient operation stage is most effective measures for reducing PN emissions [8][9][10][11][15][16][17][18]27,31,43]. Moreover, installation of the GFP in GDI engines is a straightforward pathway for reducing both the nucleation mode and the accumulation mode particles [36][37][38][39].…”
Section: Particle Matter Emissions During Vehicle Driving Testsmentioning
confidence: 99%
“…CARB has revealed that sub-23 nm particles comprise a substantial portion of the total PM emissions from GDI vehicles [5,9,21,29,30]. The primary reason for these controversial findings of differences between the particle measurement programme (PMP) methods and CARB relates to the sensitivity of the sampling and dilution approaches for the secondary particles formed from gaseous precursors [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several analyses and methods were developed [23][24][25] to assess the vehicles' emissions as a function of their age, volume capacity, type of fuel, and mean velocity. Clearly, the application of these comprehensive methods requires the knowledge of detailed data concerning the fleets of running vehicles and their yearly change.…”
Section: Introductionmentioning
confidence: 99%